Magi-1c: A Synaptic Maguk Interacting with Musk at the Vertebrate Neuromuscular Junction - Strochlic, Laure (The Rockefeller University Press, 2001)
The muscle-specific receptor tyrosine kinase (MuSK) forms part of a receptor complex, activated by nerve-derived agrin, that orchestrates the differentiation of the neuromuscular junction (NMJ). The molecular events linking MuSK activation with postsynaptic differentiation are not fully understood. In an attempt to identify partners and/or effectors of MuSK, cross-linking and immunopurification experiments were performed in purified postsynaptic membranes from the Torpedo electrocyte, a model system for the NMJ. Matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) analysis was conducted on both cross-link products, and on the major peptide coimmunopurified with MuSK; this analysis identified a polypeptide corresponding to the COOH-terminal fragment of membrane-associated guanylate kinase (MAGUK) with inverted domain organization (MAGI)-1c. A bona fide MAGI-1c (150 kD) was detected by Western blotting in the postsynaptic membrane of Torpedo electrocytes, and in a high molecular mass cross-link product of MuSK. Immunofluorescence experiments showed that MAGI-1c is localized specifically at the adult rat NMJ, but is absent from agrin-induced acetylcholine receptor clusters in myotubes in vitro. In the central nervous system, MAGUKs play a primary role as scaffolding proteins that organize cytoskeletal signaling complexes at excitatory synapses. Our data suggest that a protein from the MAGUK family is involved in the MuSK signaling pathway at the vertebrate NMJ.